Bioconversion of Gelatinised Sago Starch to Fermentable Sugar Using Recombinant Saccharomyces Cerevisiae - Mohamad Nazri, Azlian (2004)
Bioconversion of sago starch to fermentable sugar was investigated using three genetically modified Saccharomyces cerevisiae strains, YKU107 (expressing α- amylase), YKU131 (expressing glucoamylase) and YKU 132 (expressing α-amylase and glucoamylase). Alpha-amylase (YKU107) and glucoamylase (YKU131) was partial purified using acetone and ammonium sulphate precipitation, respectively before characterisation studies were carried out. The enzymes were purified by about 2.78 and 1.08 fold with recovery of 41.93% and 33.64%, respectively. Through DEAE-cellulose column chromatography, only 26.31% α-amylase and 36.68% glucoamylase were recovered with purification fold of 6.90 and 1.81. Futher characterisation showed that both enzymes were stable at pH 5.5, temperature 30oC and ionic strength of 0.05 M, evidenced with residual activity higher than 90%. Optimum pH, temperature and initial starch concentration for glucose production were determined as 5.5, 30oC and 20gL-1, respectively. From influence of various starches studied, potato starch was hydrolysed efficiently, followed by corn, sago, cassava and rice starch. However, the maximum yield of glucose based on utilised starch followed the sequence: sago > corn > potato > cassava > rice starch. Batch fermentation using 2 L fermenter showed that strains YKU107, YKU131 and YKU132 were able to hydrolyse about 97.82%, 86.86% and 88.06%, respectively during 60 hours cultivation with maximum glucose concentration of 9.32 gL-1, 3.63 gL-1 and 0.85 gL-1, respectively. Based on maximum glucose production, YKU107 was selected for futher studies. The influence of rpm examined by this strain indicated that the glucose production consistently increased with rpm. Repeatedbatch fermentation at maximum glucose concentration produced 6.91 gL-1 of glucose and 12.35 gL-1 of biomass. The continuous culture was performed in order to increase the glucose production. The maximum glucose concentration of 7.80 gL-1 was obtained at 0.075 h-1 dilution rate and suggested that the optimum operating conditions for glucose production is just at the critical dilution rate. The plasmid was categorised as stable even after 348 hours of continuous cultivation (43 residence times).